Ice Bath more effective than Proprioceptive Neuromuscular Facilitation on Blood Lactate Reduction and Heart Rate Recovery in Rock Climbing Athletes in Denpasar - Darma, I Wayan Eka Wirahadi; Susy Purnawati; I Putu Gde Surya Adhitya (PT Inovasi Pratama Internasional, 2025)
Sport is a structured and planned physical activity aimed at improving fitness and overall health. One rapidly growing discipline is rock climbing, particularly in the speed category. This high-intensity anaerobic activity often causes muscle fatigue, elevated blood lactate, and increased recovery heart rate. Excessive lactate accumulation disrupts recovery and may impair performance, making effective recovery methods essential. Two commonly used techniques are Proprioceptive Neuromuscular Facilitation (PNF) stretching and cold water immersion, or ice bath. This study compared the effectiveness of PNF stretching and ice bath in reducing blood lactate and recovery heart rate among rock climbing athletes in Denpasar City. A quasi-experimental pre-test–post-test design was conducted on three groups: PNF stretching (n=6), ice bath (n=6), and control (n=6). Interventions were performed twice weekly for two weeks. Blood lactate levels were measured with the Lactate Scout, while recovery heart rate was recorded manually at one and five minutes post-exercise. Results indicated that both PNF stretching and ice bath significantly reduced blood lactate (p<0.05) compared to control, but the ice bath produced greater and more consistent reductions. For recovery heart rate, no significant differences were found between groups (p>0.05). However, the ice bath group displayed a more favorable downward trend, suggesting potential clinical relevance. PNF stretching did not significantly affect heart rate recovery compared to ice bath or control but still demonstrated positive recovery effects. In conclusion, the ice bath method proved more effective than PNF stretching in reducing blood lactate, making it a recommended recovery strategy for speed climbing athletes. PNF stretching remains valuable for flexibility and muscular relaxation and may be best applied alongside other recovery methods. Future studies should investigate long-term outcomes, varied immersion protocols, and larger athlete populations to enhance generalizability